The effect of air pollution on deaths, disease burden, and life expectancy across China and its provinces, 1990–2017: an analysis for the Global Burden of Disease Study 2017. Issue 9 (September 2020) - Yin, Peng; Brauer, Michael; Cohen, Aaron J; Wang, Haidong; Li, Jie; Burnett, Richard T; Stanaway, Jeffrey D; Causey, Kate; Larson, Samantha; Godwin, William; Frostad, Joseph; Marks, Ashley; et al.
Summary: Background: Air pollution is an important public health concern in China, with high levels of exposure to both ambient and household air pollution. To inform action at provincial levels in China, we estimated the exposure to air pollution and its effect on deaths, disease burden, and loss of life expectancy across all provinces in China from 1990 to 2017. Methods: In all 33 provinces, autonomous regions, municipalities, and special administrative regions in China, we estimated exposure to air pollution, including ambient particulate matter pollution (defined as the annual gridded concentration of PM2·5 ), household air pollution (defined as the percentage of households using solid cooking fuels and the corresponding exposure to PM2·5 ), and ozone pollution (defined as average gridded ozone concentrations). We used the methods of the Global Burden of Diseases, Injuries, and Risk Factors Study 2017 to estimate deaths and disability-adjusted life-years (DALYs) attributable to air pollution, and what the life expectancy would have been if air pollution levels had been less than the minimum level causing health loss. Findings: The average annual population-weighted PM2·5 exposure in China was 52·7 μg/m 3 (95% uncertainty interval [UI] 41·0–62·8) in 2017, which is 9% lower than in 1990 (57·8 μg/m 3, 45·0–67·0). We estimated that 1·24 million (95% UI 1·08–1·40) deaths in China were attributable to air pollution in 2017, including 851 660 (712 002–990 271) from ambient PM2·5 pollution, 271 089 (209 882–346 561) from household air pollution from solid fuels, and 178 187 (67 650–286 229) from ambient ozone pollution. The age-standardised DALY rate attributable to air pollution was 1513·1 per 100 000 in China in 2017, and was higher in males (1839·8 per 100 000) than in females (1198·3 per 100 000). The age-standardised death rate attributable to air pollution decreased by 60·6% (55·7–63·7) for China overall between 1990 and 2017, driven by an 85·4% (83·2–87·3) decline in household air pollution and a 12·0% (1·4–22·1) decline in ambient PM2·5 pollution. 40·0% of DALYs for COPD were attributable to air pollution, as were 35·6% of DALYs for lower respiratory infections, 26·1% for diabetes, 25·8% for lung cancer, 19·5% for ischaemic heart disease, and 12·8% for stroke. We estimated that if the air pollution level in China was below the minimum causing health loss, the average life expectancy would have been 1·25 years greater. The DALY rate per 100 000 attributable to air pollution varied across provinces, ranging from 482·3 (371·1–604·1) in Hong Kong to 1725·6 (720·4–2653·1) in Xinjiang for ambient pollution, and from 18·7 (9·1–34·0) in Shanghai to 1804·5 (1339·5–2270·1) in Tibet for household pollution. Although the overall mortality attributable to air pollution decreased in China between 1990 and 2017, 12 provinces showed an increasing trend during the past 27 years. Interpretation: Pollution from ambient PM2·5 and household burning of solid fuels decreased markedly in recent years in China, after extensive efforts to control emissions. However, PM2·5 concentrations still exceed the WHO Air Quality Guideline for the entire population of China, with 81% living in regions exceeding the WHO Interim Target 1, and air pollution remains an important risk factor. Sustainable development policies should be implemented and enforced to reduce the impact of air pollution on long-term economic development and population health. Funding: Bill & Melinda Gates Foundation; and China National Key Research and Development Program.